2007
DOI: 10.2528/pier07080601
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Band Omni-Directional Antenna for Wlan Application

Abstract: Abstract-A triple-band omni-directional antenna which comprises three pairs of dipoles placed back to back and printed on a dielectric substrate is presented. A prototype is constructed and tested. The experimental results show that the 10 dB return loss bandwidth (VSWR < 2.0) in 2.4 GHz, 5.2 GHz and 5.8 GHz reaches as much as 130 MHz, 500 MHz and 200 MHz, respectively. Moreover, the radiation patterns are almost omni-directional in the azimuthal plane. Peak antenna gain is 1.63 dBi, 2.36 dBi and 1.54 dBi, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 15 publications
0
51
0
Order By: Relevance
“…However, most proposed antennas are monopoles [13][14][15][16][17][18] which usually require large grounds, so the size of the antenna is big, which increases the limits of the practical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most proposed antennas are monopoles [13][14][15][16][17][18] which usually require large grounds, so the size of the antenna is big, which increases the limits of the practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, multiband antennas for WLAN applications become a hot research point in the past decades and many technologies for miniaturized antenna with multiband functionality have been proposed [10][11][12][13][14][15][16][17][18]. However, most proposed antennas are monopoles [13][14][15][16][17][18] which usually require large grounds, so the size of the antenna is big, which increases the limits of the practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers and scholars have done lots of work on multiple band antenna research, various types of printed antennas have been reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The planar monopole antenna is often adapted to realize multiple-band operation, with various structures such as letter-like shape [1][2][3][4][5][6]12], plant-like shape [7], and fractal structures [8][9][10][11][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The lower band ranges from 2.4 to 2.484 GHz for IEEE 802.11b/g and upper band covers frequency band from 5.15-5.35/5.725-5.825 GHz for IEEE 802.11a. Nowadays, dual-band WLAN systems combining IEEE 802.11a/b/g standards are becoming more attractive [1,2]. A dual-band antenna is a key component for such communication systems [3][4][5][6][7][8][9], especially for "universal" applications, where it should be covering the whole 2.4-2.484 GHz and 5.15-5.825 GHz bands for dual-band WLAN.…”
Section: Introductionmentioning
confidence: 99%